Influence of Pretreatment Root Development Stage on success of Apexification: Forensic Dental Evaluation - Goncharuk-Khomyn, Myroslav (Journal of Dentistry Indonesia, 2019)
Clinicians have previously reported effective outcomes of apexification in cases of complicated caries or trauma; however, there is still not enough evidence of how root development stage before treatment influences the success of this procedure. Objectives: The study was performed to evaluate the influence of pretreatment root development stage on the success of apexification, with the use of a modified forensic technique for estimating odontologic age. Methods: Apexification of maxillary and mandibular permanent incisors, first molars, and premolars was provided to 43 pediatric patients with symptoms of irreversible pulp changes or signs of chronic apical periodontitis. Success of apexification was evaluated with the use of a modification of Demirjian et al.’s age estimation technique; root development stages were documented radiologically before and 12 months after treatment. Results: There was a close covariance between pretreatment tooth development stages F and G and the possibility of achieving stage H after apexification (rs = 0.87 and 0.91, respectively; p < 0.05) with an average follow-up period of 11.6 ± 0.7 months. Conclusion: Pretreatment tooth development at stages F to H, as originally proposed by Demirjian et al., was found to significantly influence the prognosis for achieving successful apexification outcome.